The value of the CHA2DS2-VASc score for refining stroke risk stratification in patients with atrial fibrillation with a CHADS2 score 0–1: A nationwide cohort study - Olesen, Jonas Bjerring; Torp-Pedersen, Christian; Hansen, Morten Lock; Lip, Gregory Y. H. (Thrombosis and Haemostasis, 2012)
North American and European guidelines on atrial fibrillation (AF) are conflicting regarding the classification of patients at low/intermediate risk of stroke. We aimed to investigate if the CHA2DS2-VASc score improved risk stratification of AF patients with a CHADS2 score of 0–1. Using individual-level-linkage of nationwide Danish registries 1997–2008, we identified patients discharged with AF having a CHADS2 score of 0–1 and not treated with vitamin K antagonist or heparin. In patients with a CHADS2 score of 0, 1, and 0–1, rates of stroke/ thromboembolism were determined according to CHA2DS2-VASc score, and the risk associated with increasing CHA2DS2-VASc score was estimated in Cox regression models adjusted for year of inclusion and anti-platelet therapy. The value of adding the extra CHA2DS2-VASc risk factors to the CHADS2 score was evaluated by c-statistics, Net Reclassification Improvement (NRI) and Integrated Discrimination Improvement (IDI). We included 47,576 patients with a CHADS2 score of 0–1, from these 7,536 (15.8%) were CHA2DS2-VASc score=0, 10,062 (21.2%) were CHA2DS2-VASc score=1, 14,310 (30.1%) were CHA2DS2-VASc score=2, 14,188 (29.8%) were CHA2DS2-VASc score=3, and 1,480 (3.1%) were CHA2DS2-VASc score=4. Of the cohort with a CHADS2 score of 0–1, the stroke/thromboembolism rate per 100 person-years increased with increasing CHA2DS2-VASc score (95% confidence interval): 0.84 (0.65–1.08), 1.79 (1.53–2.09), 3.67 (3.34–4.03), 5.75 (5.33–6.21), and 8.18 (6.68–10.02) at one year follow-up with CHA2DS2-VASc scores of 0, 1, 2, 3, and 4, respectively. Patients with a CHADS2 score=0 were not all ‘low risk’, with one-year event rates ranging from 0.84 (CHA2DS2-VASc score=0) to 3.2 (CHA2DS2-VASc score=3). Results from Cox regression analyses, NRI, and IDI confirmed the improved predictive ability of the CHA2DS2-VASc score in the AF patients who have a CHADS2 score of 0–1. In conclusion, the CHA2DS2-VASc provides critical information on risk of stroke in AF patients with a CHADS2 score of 0–1 that can aid a decision of using anti-coagulation. Even in patients categorised as ‘low risk’ using a CHADS2 score=0, the CHA2DS2-VASc score significantly improved the predictive value of the CHADS2 score alone and a CHA2DS2-VASc score=0 could clearly identify ‘truly low risk’ subjects. Use of the CHA2DS2-VASc score would significantly improve classification of AF patients at low and intermediate risk of stroke, compared to the commonly used CHADS2 score.Note: The editorial process for this article was fully handled by Prof. Christian Weber, Editor-in-Chief.
Keywords: Atrial fibrillation; epidemiology; stroke; risk score